The Red Carpet : The Unstoppable Artificial General Intelligence Models - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2024)
The present research paper provides an in-depth exploration of Artificial General Intelligence (AGI) models. This paper explores the concept of AGI, its current state of development, and its potential benefits and risks. It then delves into the history of AGI development, highlighting key milestones and breakthroughs. It also examines different approaches to AGI modelling, including symbolic AI, connectionist models, and more recent advancements in Machine Learning and deep learning. Additionally, the ethical implications of AGI development, its potential applications, and challenges associated with building AGI are discussed. Finally, the conclusion reflects on the current state of AGI research and provides insights into the future direction of this rapidly evolving field.